Intersections between COVID-19 and socio-economic mental health stressors in the lives of South African adolescent girls and young women - Zoe Duby; Brittany Bunce; Chantal Fowler; Kate Bergh; Kim Jonas; Janan Janine Dietrich; Darshini Govindasamy; Caroline Kuo; Catherine Mathews (BMC, 2022)
Abstract Background In contexts where poverty and mental health stressors already interact to negatively impact the most vulnerable populations, COVID-19 is likely to have worsened these impacts. Before the COVID-19 pandemic, adolescent girls and young women (AGYW) in South Africa already faced intersecting mental health stressors and vulnerabilities. It is critical to understand how additional challenges brought on by COVID-19 have intersected with existing vulnerabilities and mental health risks AGYW faced, particularly given the intersections between psychological distress and increased risk behaviours that impact sexual and reproductive health. We aimed to examine socio-economic and mental health impacts of COVID-19 on South African AGYW in order to understand how additional challenges brought on by COVID-19 have intersected with existing challenges, compounding AGYW vulnerabilities. Methods Using qualitative and quantitative methods, framed by the syndemic theory, we examined the intersections between mental health and the COVID-19 epidemic amongst AGYW in six districts of South Africa characterised by high rates of HIV, teenage pregnancy and socio-economic hardship. Between November 2020 and March 2021 we conducted a cross-sectional telephone survey with 515 AGYW, and in-depth interviews with 50 AGYW, aged 15 to 24 years. Results Our findings reveal how COVID-19 restrictions led to increased experiences of stress and anxiety. Poor mental health was compounded by strained family relationships, increased fear of domestic violence, household unemployment, economic stress and food insecurity. Respondents described feelings of boredom, frustration, isolation, loneliness, fear and hopelessness. However, despite the multitude of challenges, some AGYW articulated emotional resilience, describing ways in which they coped and retained hope. Conclusion Various psycho-social risk factors already disproportionally affect the mental health of AGYW in these communities; the COVID-19 pandemic intersects with these pre-existing social and environmental factors. Understanding strategies AGYW have used to positively cope with the uncertainty of COVID-19 amongst an array of pre-existing mental health stressors, is key in informing efforts to respond to their needs. Multisectoral interventions are needed to address the drivers of poor mental health among AGYW, and bolster healthy coping mechanisms; interventions seeking to mitigate the mental health impacts on this vulnerable population need to be responsive to the unpredictable pandemic environment.